The Effect of Crude Oil Price and Inflation on Algae Export in Indonesia - Muthalib, Dzulfikri Azis; Muthalib, Abd Azis; Nuryadi, Ahmad Muhlis; Arifuddin, Arifuddin; Harafah, La Ode Muhammad; Kamaluddin, Murdjani; Sahili, La Ode; Azis, Muh. Irfandy; Tambunan, Rince (International Journal of Energy Economics and Policy, 2023)
The aim of this study is to test and analyze the long-term and short-term effects of crude oil prices and inflation on algae export in Indonesia. The effects were tested using multiple cointegration regression and error correction models. Furthermore, annual time series data from 2012 to 2021 was used in this study and the results of the analysis show that in the long term, crude oil price and inflation have a positive effect on algae export. While in the short term, only crude oil price positively influences its exportation.